PENDAMPINGAN DAN IMPLEMENTASI E-FILLING UNTUK GURU SMPN KABUPATEN KAMPAR - Novianti, Serly; S, Al Khudri; Ramadansur, Rahmat (Komunitas Manajemen Kompetitif, 2024)
SMPN 1 Siak Hulu has a strategic location and is very supportive for tax reform in Indonesia. So the author carried out mentoring activities and implementation of e-filling for teachers of SMPN Kampar Regency. Given the importance of E-Filling Assistance and Implementation for Kampar Regency SMPN Teachers to support tax reform in Indonesia, the implementation of e-filling is one of the manifestations of Community Service (PKM) activities in taxation. So the author carried out mentoring activities and implementation of e-filling for teachers of SMPN Kampar Regency. The methods of activities that will be carried out in order to achieve the objectives of community service include: 1) Pretest: in the form of a questionnaire given before the mentoring activities (lectures and discussions) begin. 2) Discussion and direct dialogue: in the form of delivering e-filling material, consisting of messages (verbal and nonverbal), namely the form of information or explanations conveyed to participants. Extension Media: consists of: images or slides (PPT), namely counseling media that contains the display of counseling messages. 3) Submission of plaques from the service team to partners. 4) Postest: in the form of a questionnaire given after the counseling activity is completed. This is intended so that partners really feel the benefits of this Community Service Program activity, and can feel that the activities of this Community Service Program are incidental only, whenever they need knowledge assistance, the proposer will respond to it.